Short‐term outcomes in infants with mild neonatal encephalopathy: a retrospective, observational study - Yoshinori Aoki; Tatsuo Kono; Mikako Enokizono; Kaoru Okazaki (BMC, 2021)
Abstract Background Neonatal encephalopathy due to acute perinatal asphyxia is a major cause of perinatal brain damage. Moderate to severe neonatal encephalopathy is associated with high mortality and morbidity rates. However, the neurodevelopmental outcomes in neonates with mild neonatal encephalopathy are unclear. The primary aim of this single-center observational study was to assess the short-term outcomes in term neonates with mild neonatal encephalopathy due to perinatal asphyxia. A secondary aim was to identify predictors of poor prognosis by identifying the characteristics of these infants according to their short-term outcomes. Methods We retrospectively investigated all infants with perinatal asphyxia at Tokyo Metropolitan Children's Medical Center from January 2014 to December 2019. An abnormal short-term outcome was defined as any one of the following: seizures or abnormal electroencephalography, abnormal brain magnetic resonance imaging obtained within the first 4 weeks of life, and abnormal neurological examination findings at discharge. Results In total, 110 term infants with perinatal asphyxia during the study period were screened and 61 were diagnosed with mild neonatal encephalopathy. Eleven (18 %) of these infants had an abnormal short-term outcome. The median Thompson score at admission was significantly higher in infants with abnormal short-term outcomes than in those with normal short-term outcomes (5 [interquartile range, 4-5.5] vs. 2 [interquartile range, 1-3], p < 0.01). Receiver operating characteristic curve analysis showed that a cutoff value of 4 had high sensitivity and specificity (90.9 and 83.0 %, respectively) for prediction of an abnormal short-term outcome. Conclusions 18 % of infants with mild encephalopathy had an abnormal short-term outcome, such as abnormal brain magnetic resonance imaging findings. The Thompson score at admission may be a useful predictor of an abnormal short-term outcome in infants with mild neonatal encephalopathy.